Validitas Isi Instrumen Tes Matematika Siswa Kelas VII SMP Semester Ganjil - Pandra, Viktor; Aswarliansyah, Aswarliansyah (Jurnal Pendidikan Matematika : Judika Education, 2023)
This study aims to describe the validity of the mathematics ability test instrument of grade VII junior high school students in odd semesters. The method used was a modification of the Wilson Model and the Oriondo and Antonio Models. The results of the research show that the validity of the mathematics test instrument for odd semester class VII junior high school odd semester students based on calculations that have been adjusted to Aiken’s V validity is included in the 0.833 – 1 category with high information or can be said to be valid. The conclusion is that the mathematics test instrument for class VII midle school students in the odd semester can be categorized as valid based on content validity for use in measuring students mathematical abilities. Keywords: Test Instrument, Mathematical Ability, Content Validity